PENGARUH KOMITMEN ORGANISASIONAL TERHADAP SENJANGAN ANGGARAN DENGAN IDEOLOGI ETIS SEBAGAI VARIABEL PEMODERASI - Widodo, HY. Sri (KINERJA, 2015)
Dysfunctional Behavior, mainly Corruption, pervasively happens in Indonesia. Business people believeÃ‚Â in Ã¢â‚¬Å“The Myth of Amoral BusinessÃ¢â‚¬Â, in which the meaning of business is profit. The focus of business is to getmaximum profit because profit is perceived as an ultimate goal. Business people always separate business fromÃ‚Â ethical dimension.Ã‚Â In budgeting, dysfunctional behavior manifests in the form of Budgetary Slack. Middle and Low levelÃ‚Â managers create slack in their budget proposals by underestimating revenues and overestimating expensesÃ‚Â intentionally. The objectives of this behavior are anticipating uncertainties and increasing bonuses.Ã‚Â Dysfunctional behavior can be weakened by strengthening Ethical Ideology of managers involved inÃ‚Â budgeting. Managers with strong Ethical Ideology will behave in the best interest of the company as a whole;on the other hand, managers with weak ethical ideology will maximize their own interest in the expense ofÃ‚Â companiesÃ¢â‚¬â„¢ interest.The objective of this research is to examine the effects of organizational commitment on budgetary slackÃ‚Â and the role of ethical ideology in moderating these two variables. For this purpose, the data are collected fromÃ‚Â 187 middle level and top level private companyÃ¢â‚¬â„¢s managers via questionnaire. The result of this research showsÃ‚Â that Ethical Ideology weakens the effect of Organizational Commitment on Budgetary Slack.Keywords: organizational commitment, ethical ideology, dysfunctional behavior, budgetary slack